De novo pulmonary small cell carcinomas and large cell neuroendocrine carcinomas harboring EGFR mutations: Lack of response to EGFR inhibitors. Issue 1 (April 2015) - Le, Xiuning; Desai, Neelam V.; Majid, Adnan; Karp, Rebecca S.; Huberman, Mark S.; Rangachari, Deepa; Kent, Michael S.; Gangadharan, Sidharta P.; Folch, Erik; VanderLaan, Paul A.; Costa, Daniel B.
Highlights: EGFR mutations occur in some high-grade neuroendocrine lung cancers. EGFR protein is not expressed in EGFR mutated neuroendocrine lung cancers. Patients with neuroendocrine lung cancers don't respond to EGFR inhibitors. Abstract: Introduction: Epidermal growth factor receptor (EGFR) mutations are present in 10–20% of all non-small-cell lung cancers and predict for response to EGFR tyrosine kinase inhibitors (TKIs). However, the incidence of these mutations and their ability to predict response to TKIs in high-grade pulmonary neuroendocrine carcinomas [i.e. small cell lung cancer (SCLC) and large cell neuroendocrine carcinoma (LCNEC)] is unknown. Methods: The presence of EGFR mutations, clinicopathologic and anti-cancer therapy response data were retrospectively compiled and analyzed from a cohort of 608 patients–lung tumors to identify EGFR mutated high-grade pulmonary neuroendocrine carcinomas. We identified 126 EGFR -mutated (21.8% of 578 successful genotyped cases) lung cancers and only 2 (1.6%) were high-grade neuroendocrine carcinomas. Results: Case one was of a 63 year-old white never smoker woman with extensive stage SCLC harboring EGFR -delL747_P753insS but without EGFR protein expression. After progression on carboplatin/etoposide, the patient was treated with erlotinib and developed progressive disease with a survival <3 months from start of erlotinib. Case two was of a 73 year-old Asian 30 pack-year smoker man with metastatic LCNEC harboring EGFR -delL747_P753insQS and also lacking EGFR protein expression. The patient received first line therapy with erlotinib and had progressive disease with a survival of 4 months. Conclusions: The lack of response to EGFR TKIs in EGFR mutated de novo SCLC and LCNEC reported here may indicate that tumor differentiation affects tumor dependency on EGFR as a driver oncogene.